Exploring Medication Adherence Amongst Australian Adults Using an Extended Theory of Planned Behaviour - Liddelow, Caitlin; Mullan, Barbara; Novoradovskaya, Elizaveta (2020)
Background: This study examined the psychological predictors of general prescription medication adherence using an extended theory of planned behaviour (i.e. adding habit strength). The addition of habit strength to the model aimed to close the gap between intention and behaviour to further understand the psychological predictors of adherence. Method: In this prospective study, self-report data was collected online at two time points, 1 week apart, from 114 Australian adults and was used to explore the role of the theory of planned behaviour variables (attitude, subjective norm, perceived behavioural control and intention), and habit strength in predicting medication adherence. Hierarchical multiple regression analysis was used to explore the relationships between variables. Results: Results showed that collectively attitude, subjective norm and perceived behavioural control were unable to significantly predict intention to adhere. A ceiling effect was identified in intention. Perceived behavioural control was the only significant predictor of adherence behaviour (β = .41, p < .001). Habit strength was not found to be a significant predictor of adherence in this sample. Conclusion: The findings of this study show partial support for the predictive ability of the theory of planned behaviour in predicting intentions and medication adherence. It also adds to the growing literature showing the importance of perceived behavioural control in health behaviours. Behaviour change techniques related to enhancing self-efficacy, such as self-monitoring of the behaviour or keeping a diary, could be of use in interventions tailored to increase medication adherence.